Feminism thoughts in 20th and 21st century literary works: A comparative study - Fransiska Marsela Hambur; Nurhayati Nurhayati (Universitas Islam Sultan Agung, 2019)
One of most arguable and observable social phenomena is gender inequality which is based on feminism thoughts. Considering how literature may portray human’s life along with its values, this study is purposed to elaborate and compare how feminism thoughts and gender inequality take place in various literary works. Based on the importance of feminism thoughts and gender inequality in cross cultural literature, then there is a necessity to conduct a comparative literature study which focused on feminism thoughts. This study took four kinds of literary works, namely drama, prose (short-story), movie, and poetry. Feminism approach as sociological approach was applied in this study altogether with comparative criticism and content analysis method. This study discussed how feminism thoughts got more supports and encouragement as the century progressed. By comparing literary works from 20th and 21st century, several important findings can be drawn, namely (a) feminism thoughts are getting stronger along with the progression of century, (b) feminism thoughts always oppose gender inequality as both are always found as binary oppositions in literary work, (c) both feminism and gender-inequality live through human’s values and repetitive actions, (d) personal and familial values are crucial in order to develop feminism thoughts and gender-inequality in an individual, and (e) the change of values, especially social and cultural values can bring changes in both feminism and gender inequality phenomena.